The ratio of CD8 to Treg tumor-infiltrating lymphocytes is associated with response to cisplatin-based neoadjuvant chemotherapy in patients with muscle invasive urothelial carcinoma of the bladder. (3rd May 2016) - Baras, Alexander S.; Drake, Charles; Liu, Jen-Jane; Gandhi, Nilay; Kates, Max; Hoque, Mohamed O.; Meeker, Alan; Hahn, Noah; Taube, Janis M.; Schoenberg, Mark P.; Netto, George; Bivalacqua, Trinity J.
ABSTRACT: Introduction : Randomized controlled trials of platinum-based neoadjuvant chemotherapy (NAC) for bladder cancer have shown that patients who achieve a pathologic response to NAC exhibit 5 y survival rates of approximately 80–90% while NAC resistant (NR) cases exhibit 5 y survival rates of approximately 30–40%. These findings highlight the need to predict who will benefit from conventional NAC and the need for plausible alternatives.Methods : The pre-treatment biopsy tissues from a cohort of 41 patients with muscle invasive bladder who were treated with NAC were incorporated in tissue microarray and immunohistochemistry for PD-L1, CD8, and FOXP3 was performed. Percentage of PD-L1 positive tumor cells was measured. Tumor-infiltrating lymphocytes (TIL) densities, along with CD8 and Treg-specific TILs, were measured.Results : TIL density was strongly correlated with tumor PD-L1 expression, consistent with the mechanism of adaptive immune resistance in bladder cancer. Tumor cell PD-L1 expression was not a significant predictor of response. Neither was the CD8 nor Treg TIL density associated with response. Intriguingly though, the ratio of CD8 to Treg TIL densities was strongly associated with response ( p  = 0.0003), supporting the hypothesis that the immune system plays a role in the response of bladder cancer to chemotherapy.Discussion : To our knowledge, this is the first report in bladder cancer showing that the CD8 to Treg TIL density in the pre-treatment tissues is predictive for conventional NAC response. These findings warrant further investigations to both better characterize this association in larger cohorts and begin to elucidate the underlying mechanism(s) of this phenomenon.